Effects of vibration and hypoxia on circulating levels of angiogenic regulators in athletes - Wang, P. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This study aimed to investigate the biological response to hypoxia as a stimulus, as well as exerciseand vibration-induced shear stress, which is known to induce angiogenesis. Twenty four male wrestlers (22.3±4.2yr) participated in this study. Each subject completed eight cycle training sessions under normal conditions (NC) without vibration, NC with vibration, normobaric hypoxic conditions (HC) without vibration, and HC with vibration. Each session lasted 60 min, and sessions were held at weekly intervals in a randomized order. Five blood samples (pre-training and 0 h post-, 0.5 h post-, 1 h post-, and 4 h post-training) were taken from each subject at each training session. Hypoxia was induced by a normobaric hypoxic chamber with an altitude of 2,500 m. The mechanical forces (cycling with or without vibration) were induced by a cycling ergometer. Methods The parameters VEGF, endostatin, and matrix metalloproteinases (MMPs) were analyzed using the ELISA method. Results VEGF showed a significant increase immediately after the exercise only with exogenously induced vibrations, as calculated with separate ANOVA analysis. Endostatin increased after training under all conditions. Discussion / Conclusions A western blot analysis was performed for the determination of endostatin corresponding to the 22-kDa cleavage product of collagen XVIII. The results indicated elevated protein content for endostatin at 0 h post-exercise. MMP-2 increased in three of the four training conditions. The exception was NC with vibration. MMP-9 reached its maximum level at 4 h post-exercise. In conclusion, the results support the contention that mechanical stimuli differentially influences factors involved in the induction of angiogenesis.